The Difference of The Effects of Conventional Flowable Composite and Self-Adhering Flowable Composite on BHK-21 Fibroblast Cells - Anuj Bhardwaj; S. Sukaton; Anggi Puspitasari; Widya Saraswati (Conservative Dentistry Journal, 2018)
Background: One type of composite resin material on the market is flowable composites (FC) which has low viscosity, can be applied to areas with low stress or require good penetration such as pit and fissure sealants, restoration of class II, class III, and class V. Along with technology development, self-adhering flowable composite (SAFC) material has been developed which shorten the applications time because it combines etch, priming, and bonding in one system. The incomplete composite polymerization process can release residual monomers which affect pulp and gingiva The effects of composite materials can be seen from the viability of BHK-21 fibroblast cells after being exposed by these materials. Aims: Determine the viability of BHK-21 cells after being exposed to conventional flowable composite (CFC) and SAFC. Method: The research was in-vitro experimental laboratory with post-test only control group design. BHK-21 cell cultures were included in a 96-well microplate and divided into control group (N=16) and two treated groups (N=16). The treated group was given CFC and SAFC in a disk form with 5mm in diameter and 2,5mm in thickness, then incubated for 24 hours. MTT was given, the optical density value was read by ELISA reader and cell viability was calculated. Optical density data were analyzed using Tukey HSD to compare between groups. Results: The BHK-21 cells viabitlity of SAFC group is greater than the CFC, , indicated by the optical density SAFC (value=0.1233) and CFC (value=0.0936). Conclusion: The viability of BHK-21 cells exposed to SAFC is higher than that of CFC.